A cosmovisão no Candomblé - Nogueira, Pedro Antonio Pires (Sacrilegens, 2012)
This article does not pretend to be exhaustive, but to introduce the topic in order to stimulate research on other ways to understand the universe. Here, we present briefly the Yoruba worldview of Candomblé - a complex vision, full of symbolism and profoundly dialectical.